Argonaute‐2 Promotes miR‐18a Entry in Human Brain Endothelial Cells. Issue 3 (16th May 2014) - Ferreira, Raquel; Santos, Tiago; Amar, Arun; Gong, Alex; Chen, Thomas C.; Tahara, Stanley M.; Giannotta, Steven L.; Hofman, Florence M.
Abstract : Background: Cerebral arteriovenous malformation (AVM) is a vascular disease exhibiting abnormal blood vessel morphology and function. miR‐18a ameliorates the abnormal characteristics of AVM‐derived brain endothelial cells (AVM‐BEC) without the use of transfection reagents. Hence, our aim was to identify the mechanisms by which miR‐18a is internalized by AVM‐BEC. Since AVM‐BEC overexpress RNA‐binding protein Argonaute‐2 (Ago‐2) we explored the clinical potential of Ago‐2 as a systemic miRNA carrier. Methods and Results: Primary cultures of AVM‐BEC were isolated from surgical specimens and tested for endogenous miR‐18a levels using qPCR. Conditioned media (CM) was derived from AVM‐BEC cultures (AVM‐BEC‐CM). AVM‐BEC‐CM significantly enhanced miR‐18a internalization. Ago‐2 was detected using western blotting and immunostaining techniques. Ago‐2 was highly expressed in AVM‐BEC; and siAgo‐2 decreased miR‐18a entry into brain‐derived endothelial cells. Only brain‐derived endothelial cells were responsive to the Ago‐2/miR‐18a complex and not other cell types tested. Secreted products (eg, thrombospondin‐1 [TSP‐1]) were tested using ELISA. Brain endothelial cells treated with the Ago‐2/miR‐18a complex in vitro increased TSP‐1 secretion. In the in vivo angiogenesis glioma model, animals were treated with miR‐18a in combination with Ago‐2. Plasma was obtained and tested for TSP‐1 and vascular endothelial growth factor (VEGF)‐A. In this angiogenesis model, the Ago‐2/miR‐18a complex caused a significant increase in TSP‐1 and decrease in VEGF‐A secretion in the plasma. Conclusions: Ago‐2 facilitates miR‐18a entry into brain endothelial cells in vitro and in vivo. This study highlights the clinical potential of Ago‐2 as a miRNA delivery platform for the treatment of brain vascular diseases.